Unexpected mammalian records in the state of Maranhão - Oliveira, Tadeu Gomes de; Gerude, Rafael Gomes; Silva Júnior, José de Sousa e (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
Evidence about unexpected occurrences of mammals in the state of Maranhão are presented in order to emphasive the transitional aspect of the state. An analysis was made of the geographic distribution area of eleven species of mammals that originally did not include the State and/or did not describe the habitats where the species were found. Results showed the influence of several biomes in the composition of the local mammalian fauna, confirming the State as a transitional area among morphoclimatic domains. There were expansions in the geographic distribution of some species, as well as the record of new habitats and taxa for Maranhão.
Keywords: Mammals; Maranhão; Transitionality; Biogeography